Persepsi dan Pemaknaan Anak Muda terhadap Tayangan Konten Pemuda Tersesat di Channel YouTube Majelis Lucu Indonesia - Muhammad Gaffari (Jurnal Media dan Komunikasi, 2022)
The presence of the Pemuda Tersesat show which is broadcast through the Majelis Lucu Indonesia channel seems to create a new breakthrough that presents a collaboration between comedians and preachers on YouTube media. With the concept of answering absurd, unique, and humorous questions posed by the audience, this content became popular and attracted the attention of the audience, and gave rise to a group of fans who are also known as Pemuda Tersesat. However, on the other side, there are also parties who do not agree with the presence of this content because it is considered to be discussing religion jokingly and not seriously. The purpose of this study is to be able to answer the formulation of the problem, namely to find out the perception of youth about the Pemuda Tersesat show on the Majelis Lucu Indonesia’s YouTube channel, the reception of youth as viewers, and what the Pemuda Tersesat figure that imagines by youth viewers. To answer the research objectives, the researcher used a qualitative approach with reception analysis methods, and conducted in-depth interviews with purposively selected informants. The results of this study indicate that audience perceptions are formed through 3 factors, namely: Audience trust, partiality (Hostile Media Perception), and influence (Third Person Perception). The results of the audience receiption in this study also show how they interpret the concept of Pemuda Tersesat show and the figures of Pemuda Tersesat that they imagine. Each informant is unique in giving his own meaning, actively and creatively, which is influenced by differences in the social conditions of the audience. Keywords: Pemuda Tersesat content, youth, perception, reception, active audience